Effects of fused-ring regiochemistry on the properties and photovoltaic performance of n-type organic semiconductor acceptors. Issue 33 (8th August 2018) - Li, Xiaojun; Huang, He; Peng, Zhengxing; Sun, Chenkai; Yang, Dengchen; Zhou, Jiadong; Liebman-Pelaez, Alex; Zhu, Chenhui; Zhang, Zhi-Guo; Zhang, Zhanjun; Xie, Zengqi; Ade, Harald; et al.
Abstract : The effects of fused-ring regiochemistry on the physicochemical and photovoltaic properties of n-type organic semiconductor (n-OS) acceptors are investigated. Abstract : The effects of fused-ring regiochemistry on the physicochemical and photovoltaic properties of n-type organic semiconductor (n-OS) acceptors are investigated. Two n-OS isomers TPTC and TPTIC were prepared with different oxygen positions in the central fused-ring unit of the acceptor molecules: oxygen is connected with benzene in TPTC and it is connected with two thiophenes in TPTIC. It is found that TPTC tends to cause excessive self-aggregation with several different packing motifs or polymorphs, while TPTIC with compact alkyl chains forms well-defined crystals. The electron mobility of TPTC, which is measured by the space-charge-limited current (SCLC) method, is much lower than that of TPTIC. When blending these acceptors with the polymer PTQ10, excessive self-aggregation of TPTC leads to large phase separation and exhibits little change after thermal annealing treatment, while the intermolecular interaction in TPTIC is appropriate to achieve suitable phase separation in its blend films with PTQ10, and the stacking of both crystallites was obviously improved after thermal annealing. Thus the PSCs with TPTIC as the acceptor show a much higher power conversion efficiency (PCE) of 10.42%, in comparison with that (1.97%) of the device with TPTC as the acceptor. These results indicate that the regiochemistry of the n-OS acceptors greatly influences the aggregation behavior of the molecules, which strongly affects the performance of the PSCs, and the structure–property relationship of the materials with the regiochemistry could guide the development of high performance n-OS acceptors.